Inteligencia emocional y desempeño en los docentes de la Institución Educativa Roosevelt College durante el año 2024 - Tarrillo Perez, Jose Froilan (2025)
The main objective of this study was to determine the relationship between emotional intelligence and the performance of teachers at Roosevelt College during the year 2024. The research was developed under a quantitative, correlational and applied approach. A non-experimental cross-sectional design was used, and the population consisted of 30 teachers of the aforementioned institution. Given the small size of the population, it was decided to use a census sampling, considering all the teachers as a sample for the study, which allowed obtaining more representative and accurate results. The results showed a positive and significant correlation between emotional intelligence and teaching performance. In particular, a Spearman's Rho correlation coefficient of 0.883 was obtained, indicating a strong association between both variables. Likewise, the bilateral significance value of 0.000 (p < 0.01) allowed us to reject the null hypothesis and accept the alternative hypothesis, confirming that emotional intelligence has a notable influence on teacher performance. In conclusion, the study reaffirms the importance of the development of emotional intelligence as a key factor in optimizing educational work and improving the quality of the teaching-learning process. These findings suggest the need to implement strategies to strengthen teachers' emotional competencies,